2021
DOI: 10.1161/strokeaha.120.031386
|View full text |Cite|
|
Sign up to set email alerts
|

Outcomes of Large Vessel Occlusion Stroke in Patients Aged ≥90 Years

Abstract: Background and Purpose: Outcomes in patients ≥90 years of age with stroke due to large vessel occlusion were compared between endovascular therapy (EVT) and medical management. Methods: Of 2420 acute ischemic stroke patients with large vessel occlusion in a prospective, multicenter, nationwide registry in Japan, patients aged ≥90 years with occlusion of the internal carotid artery or M1 segment of the middle cerebral artery were included. The primary ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…Indeed, if this outcome appears globally bad for older adults and if it suggests that acute reperfusion treatments might be futile in the oldest old, we have here to keep in mind the absence of a control group in our study. In a recent study, 28.6% of the EVT group of patients with AIS aged ≥90 years old achieved an mRS score of 0–2 or returned to at least the prestroke mRS score at 3 months 36 . In a recent meta‐analysis of outcomes following EVT in observational studies using new thrombectomy devices, 30% of the AIS patients >80 achieved mRS 0‐2 at 3 months compared to 52% of patients <80 years ( p < 0.001) 37 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Indeed, if this outcome appears globally bad for older adults and if it suggests that acute reperfusion treatments might be futile in the oldest old, we have here to keep in mind the absence of a control group in our study. In a recent study, 28.6% of the EVT group of patients with AIS aged ≥90 years old achieved an mRS score of 0–2 or returned to at least the prestroke mRS score at 3 months 36 . In a recent meta‐analysis of outcomes following EVT in observational studies using new thrombectomy devices, 30% of the AIS patients >80 achieved mRS 0‐2 at 3 months compared to 52% of patients <80 years ( p < 0.001) 37 .…”
Section: Discussionmentioning
confidence: 96%
“…In a recent study, 28.6% of the EVT group of patients with AIS aged ≥90 years old achieved an mRS score of 0-2 or returned to at least the prestroke mRS score at 3 months. 36 In a recent metaanalysis of outcomes following EVT in observational studies using new thrombectomy devices, 30% of the AIS patients >80 achieved mRS 0-2 at 3 months compared to 52% of patients <80 years (p < 0.001). 37 These results were better than outcomes of AIS patients not treated with EVT in historical cohort providing further support for EVT in the oldest patients.…”
Section: Discussionmentioning
confidence: 99%
“…The same applied to those aged 90 or more years in the context of another type of reperfusion therapy, i.e. endovascular therapy, which did not increase the risk of symptomatic intracranial haemorrhage either [25].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the efficacy of MT in very old patients remains unclear. Recently, one study showed that even in patients aged >90 years, MT improves outcomes [7]. However, poor outcomes with MT have also been reported in patients >90 years of age [16].…”
Section: Discussionmentioning
confidence: 99%
“…Although clinical trials have proven the efficacy and beneficial therapeutic outcomes of endovascular therapy in patients with large-vessel occlusion (LVO) [1][2][3][4][5], its efficacy in very elderly patients, such as nonagenarians or centenarians, is yet to be established. A study reported that mechanical thrombectomy (MT) does not lead to good outcomes in patients over 80 years of age [6], whereas another stated that MT can improve outcomes in patients over 90 years of age [7]. There are even fewer reports in the literature on centenarians [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%